The Challenges of Driving School Principals in Implementing New Paradigm Learning - Bailah Bailah; Bambang Niko Pasla (Jurnal Prajaiswara, 2021)
Objective: Describe factors that influence the implementation of a new learning paradigm. This study used Edward’s policy implementation theory. According to Edward, there are four factors of policy implementation: communication, resources, disposition, and bureaucracy structure. Methods: The study used a descriptive qualitative method. The researcher applied depth interviews to collect the primary data from Kepala Sekolah Penggerak of high school and shared the google forms with teachers and school supervisors based on self-experience as a Kepala Sekolah Penggerak consultant. The sources of secondary data are school reports and literature. Results: The implementation of the new learning paradigm faced some problems. The main obstacles are forming an operational curriculum for the education unit (OCfEU), diagnostic assessment, studying the report, and framing the Pancasila student profile.